2022
DOI: 10.3389/feart.2022.833661
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Methane Released From a Destroyed Oil Platform in the Gulf of Mexico

Abstract: In 2004, destruction of a Gulf of Mexico oil platform by Hurricane Ivan initiated a discharge of oil and gas from a water depth of 135 m, where its bundle of well conductors was broken below the seafloor near the toppled wreckage. Discharge continued largely unabated until 2019, when findings partly reported herein prompted installation of a containment device that could trap oil before it entered the water column. In 2018, prior to containment, oil and gas bubbles formed plumes that rose to the surface, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…Oil slicks from the expanding offshore oil and gas development activities ( 25 ) have been deemed to occur accidentally, and research attention has largely been limited to reported cases or those around damaged or misoperated platforms ( 26 28 ). However, our time-series analyses revealed frequent oil leakages and discharges from offshore infrastructures worldwide.…”
mentioning
confidence: 99%
“…Oil slicks from the expanding offshore oil and gas development activities ( 25 ) have been deemed to occur accidentally, and research attention has largely been limited to reported cases or those around damaged or misoperated platforms ( 26 28 ). However, our time-series analyses revealed frequent oil leakages and discharges from offshore infrastructures worldwide.…”
mentioning
confidence: 99%